Teachers' Opinions Regarding the Turkish Language Proficiency of the Syrian Students in Relation to the Turkish Language Curriculum for the Primary Education Level - Ayhan Koçoğlu; Tuğba Yanpar Yelken (Anı Publishing, 2018)
The purpose of this study was to examine the opinions of the teachers about the primary school Turkish language curriculum about the Turkish language skills to the Syrian students. The study was carried out in 2017-2018 educational year with the participation of 16 primary school teachers from two different schools in Mersin. Qualitative research methodology was used for this study. Phenomenological study was chosen as a research design. The data was collected trought focus group interview technique. The obtained data were subjected to content analysis. According to the findings, it was determined that Turkish teachers stated that the Turkish language curriculum has to develop in terms of acquiring Turkish language skills to the Syrian students. Apparantly, the objectives, content, the learning experiances processes and the measurement-evaluation activities of the Turkish language curriculum should be improved for teaching Turkish to the Syrian students. Besides, it has been determined that the most serious problems faced by the teachers participating in the research in the process of teaching Turkish to the Syrian students are being "unable to communicate with Syrian students" and "having different Turkish language ability groups of Syrian students". The solution suggested to these problems are: "Syrian students should be registered according to their Turkish language skills", "improving the Turkish language skills of the Syrian students through an out-of-school training course" and "Updating the achievements of the Turkish language education program by taking Syrian students into consideration".